Modelling the Great Recession as a Bank Panic: Challenges. (6th May 2022) - Christiano, Lawrence; Dalgic, Husnu; Li, Xiaoming
Abstract : We highlight two challenges for the notion that a pure panic bank run played an important role in the dynamics in the Great Recession. First, the conclusion depends critically on ruling out any entry of new net worth into a sector experiencing a run. We find that the implied cost of entry is implausibly large, across a range of pure panic models. Second, we show that the qualitative features of run equilibria (their existence, how many there are, etc.) are highly sensitive to minor technical changes in assumptions about banker entry. We report another result that is of independent interest. In particular, we describe implementation problems associated with standard macroprudential policy tools for reducing the risk of bank panic.